The duality of reputation portability: Investigating the demand effect of imported ratings across online labor markets - Diana Tran Nhat; Laura Thäter; Timm Teubner (Electronic Markets, 2024)
Online labor platforms have been criticized for fueling precarious working conditions. Due to their platform-bound reputation systems, switching costs are prohibitively high and workers are locked-in to the platforms. One widely discussed approach to addressing this issue and improving workers' position is the portability of reputational data. In this study, we conduct an online experiment with 239 participants to test the effect of introducing reputation portability and to study the demand effect of imported ratings. We find that the volume of imported ratings stimulates demand, although to a lower degree than onsite ratings. Specifically, the effect of imported ratings corresponds to about 35% of the effect of onsite ratings. The results imply the possibility of unintended cross-market demand concentration effects that especially favor workers with high rating volumes (“superstars”).
Keywords: D260; 620; Online labor markets; Data portability; Reputation; Trust; Adverse effects; Demand concentration